Dampak Penggunaan Gadget Dan Perilaku Kecanduan Internet Terhadap Interaksi Sosial Pada Mahasiswa Universitas Muhammadiyah Mamuju - Dina, Hikma; Aqil, Muhammad; Arsyad, Muhammad; Fajariani, Nur; Junaeda, Junaeda (Journal of Management Branding, 2025)
This study aims to analyze the impact of gadget use and internet addiction behavior on social interactions in Muhammadiyah University of Mamuju students. The research method used is quantitative and the population in this study were students of Muhammadiyah University of Mamuju, the sampling technique used the Accidental sampling technique. With 95 respondents. The data collection technique used an online questionnaire via google form distributed by the researcher, processed with SPSS. The data analysis method used was validity test, reliability, multiple linear regression, t test and f test. The results of data processing on the gadget usage variable obtained a significant figure of 0.003 <0.05 and a t count of -3.023> t table of 1.986, so that partially the gadget usage variable had a significant effect on social interactions. The results of data processing of internet addiction variables obtained a significant figure of 0.003 <0.05 and a calculated t figure of -3.018> t table of 1.986, the internet addiction variable has a significant effect on social interaction in students of Muhammadiyah University of Mamuju, while the significant value of gadget use and internet addiction is 0.000 <0.05, the calculated F figure is 27.763> F table 3.095 so that simultaneously it has a significant effect on social interaction in students of Muhammadiyah University of Mamuju